2021
DOI: 10.1042/bsr20203874
|View full text |Cite|
|
Sign up to set email alerts
|

Lamin B2 promotes the progression of triple negative breast cancer via mediating cell proliferation and apoptosis

Abstract: Triple negative breast cancer (TNBC) is a more common type of breast cancer with high distant metastasis and poor prognosis. The potential role of lamins in cancer progression has been widely revealed. However, the function of lamin B2 (LMNB2) in TNBC progression is still unclear. The present study aimed to investigate the role of LMNB2 in TNBC. The cancer genome atlas (TCGA) database analysis and immunohistochemistry (IHC) were performed to examine LMNB2 expression levels. LMNB2 short hairpin RNA plasmid or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Furthermore, our study is the first to find significant upregulation of LMNB2 in EC. LMNB2 is a lamin protein known to regulate nuclear stability and gene expression [ 39 ], with noted upregulation in breast, colorectal and oesophageal cancers [ 40 , 41 , 42 ]. Our in silico study notes LMNB2 to be highly expressed in all EC subtypes, with unique upregulation in HGEC and G3 endometrioid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study is the first to find significant upregulation of LMNB2 in EC. LMNB2 is a lamin protein known to regulate nuclear stability and gene expression [ 39 ], with noted upregulation in breast, colorectal and oesophageal cancers [ 40 , 41 , 42 ]. Our in silico study notes LMNB2 to be highly expressed in all EC subtypes, with unique upregulation in HGEC and G3 endometrioid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, different studies have reported that both a decreased expression of lamin B1 [71] and an increase of lamin B2 [77] are related to bad outcome, confirming the importance to strictly maintain proper B-type lamin levels. (e) Neoplasms of the gastrointestinal tract Decrease of lamin B1 expression is linked to different type of gastrointestinal tumours, including colon carcinomas, adenomas and gastric cancers [70,78].…”
Section: (D) Breast Cancermentioning
confidence: 92%
“…In breast cancer, different studies have reported that both a decreased expression of lamin B1 [ 71 ] and an increase of lamin B2 [ 77 ] are related to bad outcome, confirming the importance to strictly maintain proper B-type lamin levels.…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The depletion of LMNB2 suppressed proliferation and induced apoptosis and inhibited tumor growth of TNBC cells in mice. The authors suggest that Lamin B2 may promote TNBC progression and could serve as a potential therapeutical target [276].…”
Section: Lamins and Cancermentioning
confidence: 99%